2018
DOI: 10.1002/jso.25183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neoadjuvant therapy on postoperative outcomes after pancreaticoduodenectomy

Abstract: NAT does not increase the overall postoperative morbidity or mortality of PD for PDA. There is a decreased likelihood of pancreatic fistulas in patients that receive neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 40 publications
3
45
0
1
Order By: Relevance
“…Indeed, in two studies, hard gland texture was more frequently observed in patients receiving NAT, and this was associated with a reduced POPF rate. 40,42 The results of this study should be interpreted in light of some limitations. First, due to its retrospective design, this study compared oncological outcomes in patients who successful proceeded to resection after NAT, but did not include outcomes of patients who may have potentially progressed or became unfit during NAT.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, in two studies, hard gland texture was more frequently observed in patients receiving NAT, and this was associated with a reduced POPF rate. 40,42 The results of this study should be interpreted in light of some limitations. First, due to its retrospective design, this study compared oncological outcomes in patients who successful proceeded to resection after NAT, but did not include outcomes of patients who may have potentially progressed or became unfit during NAT.…”
Section: Discussionmentioning
confidence: 91%
“…(n = 37, 14.7%) was associated with prolonged overall survival [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]) versus 20 months (95% CI [15][16][17][18][19][20][21][22][23][24], P = 0.049], as compared with upfront resection. Conclusion.…”
mentioning
confidence: 99%
“…Short‐term outcomes of total pancreatectomy following chemotherapy have not been evaluated previously. Although some studies indicated that morbidity and mortality rates following pancreatic resection did not increase after chemotherapy, other studies reported increased operative morbidity in patients receiving preoperative anticancer therapy. Patients who have undergone preoperative chemotherapy require time to recover before surgery; however, the most appropriate interval between chemotherapy and surgery is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant treatment, including chemotherapy or chemoradiation for borderline resectable and locally unresectable pancreatic cancer offers several advantages including: the potential to downstage tumors to enable surgical resection and better prognosis. Therefore, current consensus guidelines have recommended the use of neoadjuvant therapy for these BRPC . However, there are few studies on surgical outcomes and prognosis of PDAC with adjacent organ infiltration.…”
Section: Discussionmentioning
confidence: 99%